Implementasi Sistem Hotspot Menggunakan Mikrotik Dan Captive Portal Sebagai Media Penunjang Aktivitas Belajar - Hairil Novansyah; Sigit Candra Setya (BETRIK, 2025)
The need for internet access on campus is increasing, particularly for searching and utilizing information to support the teaching and learning process. At the Pagar Alam Institute of Technology, the current hotspot network is limited to certain rooms, such as the STAFF, LPPM, BAAK, and Multimedia Laboratory, making it difficult for all students to access it equally. This situation results in limited access to information and hinders the learning process. This research aims to design and implement a dedicated student hotspot network to expand internet access on campus. The PPDIOO (Prepare, Planning, Design, Implement, Operate, Optimize) method is used, supported by Unified Modeling Language (UML)-based system modeling tools, such as use case diagrams and activity diagrams. The Queue Tree method is used to manage and distribute bandwidth. The result of this research is a hotspot network accessible to students on campus, with a bandwidth of 512 Kbps per user. This network supports various learning activities, such as browsing, access to the SPADA and SISTA systems, and other online learning services like YouTube This implementation is expected to support the academic process and improve the quality of learning at the Pagar Alam Institute of Technology.